SMART SYSTEM KANDANG BIBIT AYAM PEDAGING MENGGUNAKAN ARDUINO MEGA 2560 R3 BERBASIS IOT - Nur Fajri, Muhammad; Rasyad, Sabilal; Abdurrahman (Teknik Elektro Polsri, 2023)
Controlling temperature, humidity, and providing proper feed and drink in broiler broiler cages are important factors in maintaining the health and growth of chickens. To improve the efficiency and quality of this control, a system was created that automatically regulates temperature, humidity, as well as feed and drink using the fuzzy method. The fuzzy method is used to process temperature and humidity sensor data and apply fuzzy logic decisions in controlling the intensity of heating lamps, fans, and feed and drink. Sensor data will be entered into a fuzzy system that has been developed, where linguistic variables such as